Developing the ARCH family model to evaluate the impact of inflation on the S&P 500 return volatility - Xie, Zhao (2014)
This study investigates to apply the ARCH family model to assess the impact of inflation on S&P 500 stock return volatility using daily data from 2004 to 2014 in the U.S. it is found that no evidence shows that the inflation has the predictive power for stock return volatility in the U.S. this finding is consist with Davis and Kutan (2003) results for the U.S. market, but disagree with Schewert (1989) who find weak effect form inflation to the stock market volatility in U.S. In addition, this paper finds the GARCH model under the Generalized error distribution has more power when modeling the conditional volatility than the traditional normal distribution assumption. Moreover, the impact of asymmetric shocks exists in the S&P 500 conditional return volatility.